2018
DOI: 10.1089/ars.2017.6994
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofStaphylococcus aureusInfection of Macrophages by CD44, Reactive Oxygen Species, and Acid Sphingomyelinase

Abstract: We showed that CD44 activation by S. aureus stimulated Asm via the formation of reactive oxygen species, resulting in ceramide release, clustering of CD44 in ceramide-enriched membrane platforms, CD44/Asm-dependent activation of Rho family GTPases, translocation of phospho-ezrin/radixin/moesin to the plasma-membrane, and a rapid rearrangement of the actin cytoskeleton with cortical actin polymerization. Genetic deficiency of CD44 or Asm abrogated these signaling events and thereby reduced internalization of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…Ceramide has previously been shown to induce lysosomal activation of cathepsin B, which is related to endoplasmic reticulum stress, autophagy, and apoptosis (Taniguchi et al, 2015;Liu et al, 2016). There might be two possible mechanisms involving ASM and α-toxin induced cathepsin B activation: first, ceramide can directly interact with cathepsin; second, fusion of S. aureus contained phagosomes with acidified lysosomes (Li et al, 2017) possibly makes α-toxin induce lysosome permeabilization and promote the translocation of cathepsins. Notably, leakage of LPS from bacteria invaded phagolysosomes or cytosolic gram-negative bacteria may activate a non-canonical NLRP3 inflammasome (Kayagaki et al, 2013).…”
Section: Asm Links Pamps With the Inflammasomementioning
confidence: 99%
“…Ceramide has previously been shown to induce lysosomal activation of cathepsin B, which is related to endoplasmic reticulum stress, autophagy, and apoptosis (Taniguchi et al, 2015;Liu et al, 2016). There might be two possible mechanisms involving ASM and α-toxin induced cathepsin B activation: first, ceramide can directly interact with cathepsin; second, fusion of S. aureus contained phagosomes with acidified lysosomes (Li et al, 2017) possibly makes α-toxin induce lysosome permeabilization and promote the translocation of cathepsins. Notably, leakage of LPS from bacteria invaded phagolysosomes or cytosolic gram-negative bacteria may activate a non-canonical NLRP3 inflammasome (Kayagaki et al, 2013).…”
Section: Asm Links Pamps With the Inflammasomementioning
confidence: 99%
“…The ability of ROS to activate different ceramide generating pathways has been extensively studied in many cell types [52,53,54,55]. Thus, a number of reports have indicated that the generation of ROS in response to various stimuli such as antileukemic agents [56], stress [57], ischemia-reperfusion [58], pathogens [59], or hypoxia [26,27] may lead to ceramide accumulation. Both nSMase and aSMase are redox-sensitive enzymes whose activities are incremented by ROS [51,53,55].…”
Section: Ceramide and Redox Signalingmentioning
confidence: 99%
“…These events trigger activation of ASMase with formation of Cer‐enriched platform, which induces recruitment and further activation of CD44. This positive feedback loop induces a downstream signaling cascade resulting in recruitment of ERM complex at PM that, in turn, mediates bacterial internalization and killing …”
Section: Ceramide and Ceramide 1‐phosphatementioning
confidence: 99%